Influence of Moringa Oleifera leaf extract and synbiotic supplementation on mitigating stress of broilers subjected to high stocking density. - Ragab, Rasha; Hassan, Abdelrahim H.A.; Emeash, Hosney H.; Khalil, Fatma (Journal of Advanced Veterinary Research, 2024)
Environmental factors such as stocking density can cause stress and negatively affect the physiological status and meat quality of broiler chickens. In the current study, we evaluated the effects of increased rearing density on the growth performance, stress, fear levels, meat quality and liver histopathology of broilers as well as suggesting a use of different supplementations that may be helpful to reverse such adverse effects. Three hundred sixty one day-old cobb broilers (44.0 ± 5.24 g live-weights) were randomly distributed to 24 replicate pens to create two different stocking densities (D10 and D15 bird/m2) with the different supplementation treatments: 1) 10 birds/m2/pen (without any treatment, control, "CD10"), 2) 10 birds/m2/pen (moringa aqueous extract treatment "MAED10"), 3) 10 birds/m2/pen (synbiotic "SynD10"), 4)15 birds/m2/pen (without any treatment control SD15 "CD15"), 5) 15 birds/m2/pen (moringa aqueous extract treatment "MAED15"), 6) 15 birds/m2/pen (synbiotic "SynD15"). Results of the current study revealed that there was a significant increase in the overall experimental period body weight gain (P<0.01) with increasing density without affecting feed intake, body weight and feed conversion ratio. High stocking density resulted in significantly increased corticosterone (P>0.001), altered brain monoamines, deteriorated some carcass quality parameters and declined liver health. Additionally, it was concluded that moringa aqueous extract (MAE) and synbiotic (Syn) supplementation have a significant effect in reversing the catastrophic effect of high stocking density (SD) with minimal effect at the lower density groups.